Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1063/1.3275807
|View full text |Cite
|
Sign up to set email alerts
|

Proton migration mechanism for the instability of organic field-effect transistors

Abstract: During prolonged application of a gate bias, organic field-effect transistors show an instability involving a gradual shift of the threshold voltage toward the applied gate bias voltage. We propose a model for this instability in p-type transistors with a silicon-dioxide gate dielectric, based on hole-assisted production of protons in the accumulation layer and their subsequent migration into the gate dielectric. This model explains the much debated role of water and several other hitherto unexplained aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
58
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 20 publications
2
58
0
Order By: Relevance
“…11 Recently, we proposed a mechanism for the bias-stress effect in p-type field-effect transistors with SiO 2 gate dielectric that is based on production of protons from holes and water in the accumulation layer of the semiconductor and the subsequent migration of these protons into the gate dielectric. 14 We showed that this mechanism can quantitatively explain the measured dependence of the thresholdvoltage shift on time and that this dependence can indeed be accurately fitted with a stretched-exponential function. We concluded that to a good approximation the drift contribution to the motion of the protons can be neglected so that this motion is governed by diffusion.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…11 Recently, we proposed a mechanism for the bias-stress effect in p-type field-effect transistors with SiO 2 gate dielectric that is based on production of protons from holes and water in the accumulation layer of the semiconductor and the subsequent migration of these protons into the gate dielectric. 14 We showed that this mechanism can quantitatively explain the measured dependence of the thresholdvoltage shift on time and that this dependence can indeed be accurately fitted with a stretched-exponential function. We concluded that to a good approximation the drift contribution to the motion of the protons can be neglected so that this motion is governed by diffusion.…”
Section: Introductionmentioning
confidence: 96%
“…In this approximation, the time scale of the bias-stress effect is determined by a characteristic time that depends only on the diffusion coefficient and the ratio between the proton density in the oxide at the interface with the semiconductor and the hole density in the accumulation layer of the semiconductor. 14 A unique aspect of this mechanism is that not only the amount of protons stored in the dielectric is important but also their specific density profile. As a consequence, unlike other mechanisms, this mechanism predicts the occurrence of memory effects related to the biasing history of the transistor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bias stress has been ascribed mainly to migration and reversible trapping of cations, specifically protons, at the dielectric/semiconductor interface. 27 In the vacuum, bias stress still exists, suggesting the existence of an intrinsic component to this phenomenon. Although the transversal field may not be strong, being at its maximum on the order of 10 5 volt/cm, yet it may couple to the charge carriers through polarization, leading to local structural changes and energy lowering of the charged state.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold- voltage shift could be quantitatively described by assuming the production of protons (H þ ) from holes and water and the subsequent migration of these protons into the gate dielectric. 11 We note that even under vacuum conditions, water is expected to be present in the form of a monolayer adsorbed onto the SiO 2 surface.…”
mentioning
confidence: 99%